THE ROLE OF PERCEPTION OF ACCOUNTING INFORMATION SYSTEM QUALITY IN IMPROVING EMPLOYEE PERFORMANCE: A LITERATURE STUDY - Shally Amalia Nur’aini; Ishak Awaluddin; Erwin Hadisantoso (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The purpose of this study is to analyze how employees' perceptions of the quality of Accounting Information Systems (AIS) affect their work in the banking industry. Through qualitative research using interviews and feedback questionnaires with employees of the Regional Development Bank (BPD) of Southeast Sulawesi, this study concluded that positive perceptions of the AIS—in terms of ease of use, speed of access, and clarity of information—have a positive impact on employee productivity, efficiency, and effectiveness. Although this study was conducted at a single institution with a small sample size and a non-quantitative approach, it still provides a theoretical contribution to the development of an integrative model that highlights the importance of psychological factors in the successful implementation of information systems. Suggestions for future research include examining the use of quantitative methods with a longer sample size and investigating mediating or moderating variables such as job training and organizational culture.